2017
DOI: 10.4103/ijo.ijo_542_17
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of bilateral tractional retinal detachment following snakebite

Abstract: A 13-year-old female presented with diminution of vision in both eyes for 3 months following snakebite. Best-corrected visual acuities were hand movement in both eyes. Fundoscopy showed vitreous hemorrhage, and B-scan ultrasonography revealed an underlying tractional retinal detachment (TRD) involving the macula in both eyes. Patient underwent 25-gauge pars plana vitrectomy in conjunction with belt buckling, endolaser, and silicone oil tamponade in the left eye. At 6 weeks postoperatively, best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Common symptoms are central retinal artery occlusion (CRAO) [ 29 , 30 , 31 , 32 ], retinal or vitreous hemorrhage [ 33 ], and macular infarction [ 33 ]. A rare case even reported that a 13-year-old boy was diagnosed with retinal detachment after snakebite [ 34 ]. Even after receiving immediate treatment for posterior complications, most patients claim their vision is not the same as it was.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Common symptoms are central retinal artery occlusion (CRAO) [ 29 , 30 , 31 , 32 ], retinal or vitreous hemorrhage [ 33 ], and macular infarction [ 33 ]. A rare case even reported that a 13-year-old boy was diagnosed with retinal detachment after snakebite [ 34 ]. Even after receiving immediate treatment for posterior complications, most patients claim their vision is not the same as it was.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%